In situ atom trapping of Bi on W-coated slotted quartz tube flame atomic absorption spectrometry and interference studies - Kilinc, Ersin; Bakirdere, Sezgin; Aydin, Firat; Ataman, O. Yavuz (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Analytical performances of metal coated slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS) and slotted quartz tube in situ atom trapping flame atomic absorption spectrometry (SQT-AT-FAAS) systems were evaluated for determination of Bi. Non-volatile elements such as Mo, Zr, W and Ta were tried as coating materials. It was observed that W-coated SQT gave the best sensitivity for the determination of Bi for SQT-FAAS and SQT-AT-FMS. The parameters for W-coated SQT-FAAS and W-coated SQT-AT-FAAS were optimized. Sensitivity of FAAS for Bi was improved as 4.0 fold by W-coated SQT-FAAS while 613 fold enhancement in sensitivity was achieved by W-coated SQT-AT-FAAS using 5.0 min trapping with respect to conventional FAAS. MIBK was selected as organic solvent for the re-atomization of Bi from the trapping surface. Limit of detection values for W-coated SQT-FAAS and W-coated SQT-AT-FAAS was obtained as 0.14 mu g mL(-1) and 0.51 ng mL(-1), respectively. Linear calibration plot was obtained in the range of 2.5-25.0 ng mL(-1) for W-coated SQT-AT-FAAS. Accuracy of the W-coated SQT-AT-FAAS system was checked by analyzing a standard reference material, NIST 1643e. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Metal coating; Bismuth; In situ atom trapping; Atomic absorption spectrometry; Slotted quartz tube; HYDRIDE-GENERATION; SENSITIVITY IMPROVEMENT; ONLINE PRECONCENTRATION; LEAD; CADMIUM; ANTIMONY; ELEMENTS; SAMPLES; COPPER; Spectroscopy